Interviews with digital seniors: ICT use in the context of everyday life. Issue 5 (3rd May 2016) - Quan-Haase, Anabel; Martin, Kim; Schreurs, Kathleen
ABSTRACT: The literature on the digital divide suggests that seniors continue to lag behind in access to the Internet, digital skills, and engagement in various online activities. Much of the research, however, gains insight from large-scale survey research and neglects to examine the challenges and opportunities that digital seniors, those who are connected, experience in their everyday use of information and communication technologies (ICTs). We employed the theoretical lens of ICT use in the context of everyday life to inform this study. Twenty-one digital seniors (60 +) took part in interviews about how ICTs influenced their routines and practices such as news consumption, library use, information seeking, and reading. The interviews were transcribed and analyzed using grounded theory. Three key findings emerged. First, digital seniors are developing new practices and routines around their ICT use; these are novel and emerge out of ICTs' affordances. Second, digital seniors are creating hybrid practices, where they seamlessly combine traditional habits with new ones emerging from ICT use. Finally, digital seniors are recreating existing practices with digital means, i.e. the digital enhances or sometimes even replaces traditional practices. We find that agency is central to our understanding of digital seniors' adoption and use of ICTs, they critically consider various options, and make choices around their preferences, convenience of use, and affordability. For digital seniors, ICT use is not a binary because they want to have the flexibility to choose for themselves under what circumstances and for what purposes the use of ICTs is appropriate.